19.8k views
3 votes
Given f(x) = 3x - 1 and g(x) = 2x + 1, find (f +g)(3)

User Flauwekeul
by
4.8k points

1 Answer

5 votes

Answer:

(f + g)(3) = 15

Explanation:

f(x) = 3x - 1

g(x) = 2x + 1

To find (f +g)(3) , first find (f + g)(x)

To find (f + g)(x) add g(x) to f(x)

That's

(f + g)(x) = 3x - 1 + 2x + 1

= 3x + 2x + 1 - 1

(f + g)(x) = 5x

Now to find (f + g)(3) substitute 3 into

(f + g)(x)

That's

(f +g)(3) = 5(3)

(f + g)(3) = 15

Hope this helps you

User Satara
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.